KORELASI PEMAHAMAN SISWA TENTANG MATERI ETIKA PERGAULAN DALAM ISLAM PADA MATA PELAJARAN AKIDAH AKHLAK TERHADAP PENERAPAN ADAB BERGAUL KEPADA TEMAN SEBAYA - Muhammad Surya Pratama; Risnawati Risnawati; Miftahir Rizqa (TABYIN: JURNAL PENDIDIKAN ISLAM, 2025)
This research aimed at testing the correlation of students’ comprehension of Social Ethics in Islam material on Akidah Akhlak subject toward their application of social ethics to peers. It was correlation research with quantitative approach. 364 students were the population of this research. Purposive sampling technique, sampling technique with certain considerations, was used in this research because Social Ethics in Islam material was only available at the twelfth grade. Test, questionnaire, and documentation were the instruments of collecting data. Serial correlation was the technique of analyzing data. The research findings showed that the serial correlation coefficient score 0.417 was higher than rtable at 5% and 1% significant levels, 0.266<0.417>0.345. Therefore, Ha was accepted, and it meant that there was a significant correlation of students’ comprehension of Social Ethics in Islam material toward their application of social ethics to peers with the correlation degree that was moderate, and the contribution of students’ comprehension of Social Ethics in Islam material toward their application of social ethics to peers was 17.39%, and 82.61% was correlation by other variables.